2020
DOI: 10.3389/fpsyg.2020.570017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-19 on the Perception of Academic Self-Efficacy, State Anxiety, and Trait Anxiety in College Students

Abstract: The worldwide pandemic situation caused by coronavirus disease 2019 (COVID-19) has led to a state of confinement of the population, which has caused, following consulted research, an increase in stress. Faced with this situation, the Spanish university not only had to adapt to the changes derived from the causes of the pandemic but also had to face a new methodological model—e-learning teaching—for which not all teachers and students were prepared. This could cause an increase in stress due to the uncertainty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
127
4
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 35 publications
9
127
4
4
Order By: Relevance
“…Interestingly, the RESE results showed improvements on self-efficacy. In 2020, Alemany-Arrebola et al demonstrated that the worldwide pandemic situation has caused an increase in stress and also showed that a stressful situation (pandemic and confinement) together with a critical event (COVID-19), increases anxiety levels and influences the perception of self-efficacy [ 44 ]. Although the connection between self-esteem and regular physical activity is well documented, Dominski et al (2020) showed a connection between CrossFit training and higher levels of psychological functioning (well-being, affect, body awareness, and self-esteem) [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the RESE results showed improvements on self-efficacy. In 2020, Alemany-Arrebola et al demonstrated that the worldwide pandemic situation has caused an increase in stress and also showed that a stressful situation (pandemic and confinement) together with a critical event (COVID-19), increases anxiety levels and influences the perception of self-efficacy [ 44 ]. Although the connection between self-esteem and regular physical activity is well documented, Dominski et al (2020) showed a connection between CrossFit training and higher levels of psychological functioning (well-being, affect, body awareness, and self-esteem) [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…If we adopt the approach of whole-person development (physical, socio-moral, motor, cognitive and linguistic), studying the impact in these different aspects should be of interest. Also of interest are peer relations mediated by technology, as well as the impact on pre-existing problems in this area, such as cyberbullying, sexting, and so on ( Alemany-Arrebola et al, 2020 ). We analyze how this experience of stress produces effects in different stages of education, as well as how to address and promote behavioral health, based on models that have contributed empirical evidence.…”
Section: The Role Of Educational Psychology As An Applied Science Wimentioning
confidence: 99%
“…Effects within the family context are important when detecting problem areas and establishing guidelines for intervention. Also important is the effect on academic achievement and construction of scholastic and academic competencies, including the areas of special educational needs and attention to diversity ( Alemany-Arrebola et al, 2020 ; Martarelli et al, 2020 ; Zaccoletti et al, 2020 ).…”
Section: The Role Of Educational Psychology As An Applied Science Wimentioning
confidence: 99%
“…Some studies have already shown how the confinement situation in different countries has been associated with anxiety, mood changes, changes in daily life patterns (including increased consumption of tobacco and alcohol, longer exposure to screens, etc.) and worsening health-related behaviors, among other variables ( Alemany-Arrebola et al, 2020 ; López-Bueno et al, 2020a , b ; Smith et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%